Identification and evaluation of a pinocembrin analog as a TRPV1 inhibitor with analgesic properties in murine pain models - Chen, Hanbin; Li, Guanghong; Deng, Lin; Xu, Nan; Lee, Simon Ming-Yuen; Nie, Xiaowei; Bian, Jin-Song (Frontiers in Pharmacology, 2025)
IntroductionPain is a complex phenomenon involving physiological and psychological responses to noxious stimuli. Long-term opioid or NSAID use leads to reduced efficacy and tolerance. Initially a thermosensitive receptor, TRPV1 is increasingly recognized as a target for analgesic intervention.MethodsOur investigation is focused on the exploration of novel TRPV1 antagonists derived from natural sources through computational screening methodologies, aiming to assess their efficacy as analgesic agents.ResultsAmong the compounds screened, a promising TRPV1 antagonist named pinocembrin-7-o-3-o-galloyl-4-6-hexahydroxydiphenoyl-beta-d-glucoside (PINO) has exhibited superior stability in its interaction with TRPV1 through virtual screening and molecular dynamics simulation. A dosage of 20 mg/kg of PINO had been shown to reduce the writhing response in acetic acid-induced mice, elevate the thermal pain threshold in the hot water tail-flick and hot plate assays, and concurrently increase the mechanical pain threshold in CFA-induced inflammatory pain models in mice. Moreover, in a murine Lewis lung carcinoma cell line LL-induced bone cancer pain model, PINO also effectively raised the thermal and mechanical pain thresholds in mice. Furthermore, PINO had been found to attenuate the production and gene expression of pro-inflammatory cytokines. The underlying mechanism was attributed to the suppression of NF-κB and MAPK signaling cascades.DiscussionThis innovative compound represents a prospective avenue for the management of acute, chronic, and bone cancer pain, providing a viable alternative analgesic option for individuals suffering from such conditions.